Short-term treatment with a novel HIF-prolyl hydroxylase inhibitor (GSK1278863) failed to improve measures of performance in subjects with claudication-limited peripheral artery disease. (December 2014) - Olson, Eric; Demopoulos, Laura; Haws, Thomas F; Hu, Erding; Fang, Zixing; Mahar, Kelly M; Qin, Pu; Lepore, John; Bauer, Timothy A; Hiatt, William R
Hypoxia inducible factor (HIF) stabilization by HIF-prolyl hydroxylase (PHD) inhibitors may improve ischemic conditions such as peripheral artery disease (PAD). This multicenter, randomized, placebo-controlled study evaluated the safety and efficacy of GSK1278863 (an oral PHD inhibitor) in subjects with PAD. The study assessed two active treatment paradigms: single dosing and subchronic daily dosing (300 mg single dose and 15 mg daily for 14 days, respectively). Neither regimen improved exercise performance compared with placebo (change from baseline in the 6-minute walk test (6MWT; feet), (GSK1278863, placebo): single dose (–46, –44), p =0.96; repeat dose (9, 8), p =0.99; change in number of contractions to onset of claudication (goniometry): single dose (4, –1), p =0.053; repeat dose (–2, 1), p =0.08). A calf-muscle biopsy substudy showed no increases in mRNA or protein levels of HIF target genes. More subjects receiving GSK1278863 than placebo experienced adverse events, particularly following the 300 mg single dose. Thus, assessing the safety of GSK1278863 in this setting would require a larger population exposed to the agent for a longer duration. These data do not support a benefit of GSK1278863 in PAD using the regimens tested.ClinicalTrials.gov Identifier: NCT01673555